UNDERSTANDING THE CONCEPT: FOUNDATIONS OF LINGUOCULTURAL STUDIES (Conferencea, 2024)
This article delves into the foundational concepts of linguocultural studies, with a particular focus on the distinction between "concept" and "notion." It examines how cognitive linguistics and pragmatics contribute to our understanding of language as a cultural and cognitive phenomenon. The study emphasizes the importance of understanding concepts as complex, culture-specific mental constructs that shape and reflect the worldview of a society. Drawing on the work of key scholars in the field, such as D.S. Likhachev and Yu.S. Stepanov, the article explores the relationship between language and culture through the lens of concepts, arguing that they are essential to understanding human cognition and social interaction. The article also highlights how linguocultural analysis can provide valuable insights into national identity and cultural heritage.